2022
DOI: 10.3389/fmedt.2022.1068972
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation reactions of cellular and acellular hemoglobins: Implications for human health

Abstract: Oxygen reversibly binds to the redox active iron, a transition metal in human Hemoglobin (Hb), which subsequently undergoes oxidation in air. This process is akin to iron rusting in non-biological systems. This results in the formation of non-oxygen carrying methemoglobin (ferric) (Fe3+) and reactive oxygen species (ROS). In circulating red blood cells (RBCs), Hb remains largely in the ferrous functional form (HbF2+) throughout the RBC's lifespan due to the presence of effective enzymatic and non-enzymatic pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 49 publications
(59 reference statements)
0
5
0
Order By: Relevance
“…Briefly, Hb is a heterotetramer (α 2 β 2 ) with each subunit harboring a heme cofactor that is capable of binding O 2 in solution when the heme iron is in a ferrous (Fe 2+ ) state. 35,36 Importantly, the oxidation and ligand-bound states of Hb can be readily monitored using UV-vis spectroscopy (Figure 1B) and further verified using cryoEM. [37][38][39] We first elected to limit the amount of O 2 that enters the sample prior to loading in the chameleon dispenser.…”
Section: Resultsmentioning
confidence: 81%
“…Briefly, Hb is a heterotetramer (α 2 β 2 ) with each subunit harboring a heme cofactor that is capable of binding O 2 in solution when the heme iron is in a ferrous (Fe 2+ ) state. 35,36 Importantly, the oxidation and ligand-bound states of Hb can be readily monitored using UV-vis spectroscopy (Figure 1B) and further verified using cryoEM. [37][38][39] We first elected to limit the amount of O 2 that enters the sample prior to loading in the chameleon dispenser.…”
Section: Resultsmentioning
confidence: 81%
“…Hydrogen peroxide is the most abounded oxidant in vivo and its release has been associated with hemolytic conditions [ 34 , 35 ]. As a result of their pseudoperoxidase catalytic activity, heme and some hemoproteins catalytically degrade hydrogen peroxide, a process that can be accompanied by formation of hyperoxidized heme species [ 36 , 38 , 39 , 40 , 41 ]. As previously described, [ 28 , 29 ] the exposure of human polyclonal IgG to heme (Fe 3+ ) resulted in an increase of Ab binding to human proteins ( Figure 1 a).…”
Section: Resultsmentioning
confidence: 99%
“…Under inflammatory conditions, hydrogen peroxide and hypochlorous acid are generated in large quantities by polymorphonuclear cells [ 69 ]. Accordingly, it has been observed that in hemolytic conditions, oxidized forms of heme are generated in vivo [ 36 , 37 , 41 , 51 ]. Therefore, it is most likely that in such pathological situation Abs experience the effects not only of heme (Fe 3+ ) but also of its oxidation derivatives.…”
Section: Discussionmentioning
confidence: 99%
“…The regulation of these iron ion-containing molecules is tightly controlled as their dysregulation may be harmful to human health [12,[25][26][27][28][29][30], as heme also appears to have toxic properties [31]. Further evidence for the tight regulation of iron ions during pregnancy [32], exercise [33], and hypoxia [34] indicate that this ion is very important biologically.…”
Section: Incorporation Of Ferro-magnetic Ions In Essential Systems An...mentioning
confidence: 99%